Organizational readiness and its contributing factors to adopt KM processes: a conceptual model - Mohamed Jalaldeen , Mohamed Razi; Abdul Karim, Nor Shariza; Mohamed, Norshidah (IBIMA Publishing, 2009)
The main purpose of this paper is to propose a conceptual model that can be used to assess the organizational readiness and its contributing factors for KM process adoption. The authors propose that the organizational readiness should be assessed considering both organizational and individual factors. The model has been developed by integrating KM infrastructure and Unified Theory of Acceptance and Use of Technology (UTAUT). This model will enrich the KM literature, especially on KM readiness, while being the basis for other researchers and authors to develop further.